A Study on Dynamic Links between Resources, Work Engagement and Job Performance in Academia of Pakistan - Khan, Anwar; Md Yusoff, Rosman Bin (International Review of Management and Marketing, 2016)
Highly competitive workplace trends of twenty first century have set new performance standards for academic staff. Now the academicians are expected to engage in multiple tasks resultantly they need extra energies and skills. The motivational hypothesis of Job Demands-Resources model states that resources play a vital role in installing energies and Performance. Following this proposition, the current study examined dynamic linkages between Resources, Work Engagement and Job Performance of academic staff working in universities of Pakistan. Using a cross section survey design, self reported data was collected on variables of Demographics, Resources, Work Engagement and Job Performance from 1184 academic staff working with 12 universities of Pakistan. Demographic data were analyzed by descriptive statistics, whereas Structural Equation Modeling was performed to know the linkages between selected variables. The demographic results revealed that the majority of academic staff were married, within the age of 20 to 40 years and were holding job positions of Lecturers and Assistant Professors, thus their job experience was between 05 to 15 years. The results of Structural Equation Modeling showed that Resources were significantly linked to Work Engagement and Work Performance, where Work Engagement acted as a mediator variable between Resources and Work Performance variables. It is concluded that resources are vital elements of better performance. Therefore, efforts should be directed towards the appropriate acquisition, distribution and utilization of resources, so that the Job Performance of teaching staff in Pakistan could be enhanced to the desired level. Keywords: Job Performance, Work Engagement, Resources, Academia JEL Classifications: M1, M3